Dissecting recipient from donor contribution in experimental kidney transplantation: focus on endothelial proliferation and inflammation - Papazova, Diana A. (Dis Model Mech, 2018)
Kidney transplantation (Tx) is considered the only definite treatment for end-stage kidney disease (ESKD) patients. The increasing prevalence of ESKD has necessitated the introduction of transplantation with kidneys from suboptimal donors. There is, however, still a lack of fundamental and longitudinal research on suboptimal kidney transplants. Specifically, there is a demand for accurate pre-Tx predictors of donor kidney function and injury to predict post-Tx outcome. In the present study, we combine rat models of chronic kidney disease (CKD) and renal Tx to dissect the effects of healthy and CKD renal grafts on healthy and CKD recipients. We show that renal function at 6 weeks post-Tx is exclusively determined by donor graft quality. Using cell tracking within enhanced green fluorescent protein-positive (eGFP(+)) recipients, we furthermore show that most inflammatory cells within the donor kidney originate from the donor. Oxidative and vascular extra-renal damage were, in contrast, determined by the recipient. Post- versus pre-Tx evaluation of grafts showed an increase in glomerular and peritubular capillary rarefaction in healthy but not CKD grafts within a CKD environment. Proliferation of glomerular endothelium was similar in all groups, and influx of eGFP(+) recipient-derived cells occurred irrespective of graft or recipient status. Glomerular and peritubular capillary rarefaction, severity of inflammation and macrophage subtype data post-Tx were, however, determined by more complicated effects, warranting further study. Our experimental model could help to further distinguish graft from recipient environment effects, leading to new strategies to improve graft survival of suboptimal Tx kidneys. This article has an associated First Person interview with the first author of the paper.